PESANTREN: TANTANGAN DAN MASA DEPAN DAKWAH - Jabbar, Abdul (Tasamuh: Jurnal Studi Islam, 2018)
Islamic school is an education institutional of Islam that functions as center of education and transmission of Islam (preaching). There are five elements of Islamic school, among one and another cannot be separated. The five of this element include an Islamic religious teacher, religious pupil, Islamic boarding school, mosque, and teaching of classical holy book, or it can be mentioned as yellowâs holy book. The process of inherent preaching in education is conducted in Islamic school environment. The problematic of preaching is the challenge and the preachingâs future for the Islamic boarding school that is required to be an institutional of preaching and Islam education but also following as the development. Thus, Islamic school is not only recognized as traditional, but it is able to be institutional modern of preaching and education that has three transmission functions of Islamic knowledge, maintenance of Islamic tradition and development of Islamic Teacher.